2022
DOI: 10.3389/fonc.2022.827956
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of m6A RNA Methylation Regulators in Gynecological Cancer

Abstract: Gynecological cancers seriously affect the reproductive system of females; diseases include ovarian tumors, uterine tumors, endometrial cancers, cervical cancers, and vulva and vaginal tumors. At present, the diagnosis methods of gynecological cancer are insufficiently sensitive and specific, leading to failure of early disease detection. N6-methyladenosine (m6A) plays various biological functions in RNA modification and is currently studied extensively. m6A modification controls the fate of transcripts and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 114 publications
(117 reference statements)
0
18
0
Order By: Relevance
“…More recently, extensive efforts have been made to investigate the biological effects of dysregulated m6A modifications and related mechanisms (i.e., m6A writers, erasers, and reader proteins) in various cancers, such as prostate cancer ( Wang et al, 2022 ), colorectal cancer ( Tanabe et al, 2016 ; Zhu et al, 2020b ), gastric cancer ( Xu et al, 2021 ), esophageal cancer ( Guo et al, 2020 ), cervical cancer and endometrial cancer ( Zhang and Yang, 2021 ; Huang et al, 2022 ), pancreatic cancer ( Li et al, 2021 ), skin cancer ( Yang et al, 2021 ), etc. Moreover, METTL16, as an independent regulator, plays an important role in RNA m6A modification.…”
Section: Part 2: the Role Of M6a Modification In Cancermentioning
confidence: 99%
“…More recently, extensive efforts have been made to investigate the biological effects of dysregulated m6A modifications and related mechanisms (i.e., m6A writers, erasers, and reader proteins) in various cancers, such as prostate cancer ( Wang et al, 2022 ), colorectal cancer ( Tanabe et al, 2016 ; Zhu et al, 2020b ), gastric cancer ( Xu et al, 2021 ), esophageal cancer ( Guo et al, 2020 ), cervical cancer and endometrial cancer ( Zhang and Yang, 2021 ; Huang et al, 2022 ), pancreatic cancer ( Li et al, 2021 ), skin cancer ( Yang et al, 2021 ), etc. Moreover, METTL16, as an independent regulator, plays an important role in RNA m6A modification.…”
Section: Part 2: the Role Of M6a Modification In Cancermentioning
confidence: 99%
“…Many studies have shown that m6A modifications are characteristic of tumor development. Remarkably, the m6A modification patterns in the pathogenesis of tumors, such as uveal melanoma [42,73,321], retinoblastoma [317], and glioblastoma [322,323], female reproductive system cancers [324], acute myeloid leukemia [325], breast cancer [326], prostate cancer [327], liver cancer [57,328], lung cancer [329], pancreatic cancer [330], colorectal cancer [331], kidney cancer [332], and gastric cancer [333] are highly variable. The role of m6A modifications in cancer genesis is controversial.…”
Section: Implication Of M6a Modification In Improving Precision Medic...mentioning
confidence: 99%
“…m 6 A-binding proteins mainly include YT521-B homology (YTH) domain-containing proteins (YTHDC1, YTHDC2, YTHDF1, YTHDF2 and YTHDF3), heterogeneous nuclear ribonucleoprotein (hnRNP) family members (hnRNPA2/B1, hnRNPC and hnRNPG), FXR family members, IGF2BP family members, eIF family members and G3BPs family members [ 26 , 38 ]. The main characteristic of m 6 A-binding proteins is that they all have a conserved m 6 A-binding domain and bind to the RRm6ACH sequence [ 39 , 40 ].…”
Section: Molecular Mechanisms Of M 6 a Modificationmentioning
confidence: 99%